Hypotension, Syncope, and Fever in Systemic Mastocytosis without Skin Infiltration and Rapid Response to Corticosteroid and Cyclosporin: A Case Report - Didem Ozdemir; Selcuk Dagdelen; Tomris Erbas; Kemal Agbaht; Songul Serefhanoglu; Salih Aksu; Sibel Ersoy-Evans (Case Reports in Medicine)
Mast cell disorders are defined by an abnormal accumulation of tissue mast cells in one or more organ systems. In systemic mastocytosis, at least one extracutaneous organ is involved by definition. Although, systemic mastocytosis usually represents with skin lesion called urticaria pigmentosa, in a small proportion, there is extracutaneous involvement without skin infiltration. Other manifestations are flushing, tachycardia, dyspepsia, diarrhea, hypotension, syncope, and rarely fever. Various medications have been used but there is not a definite cure for systemic mastocytosis. The principles of treatment include control of symptoms with measures aimed to decrease mast cell activation. We describe a case of systemic mastocytosis presenting with hypotension, syncope attacks, fever, and local flushing. In bone marrow biopsy, increased mast cell infiltration was demonstrated. She had no skin infiltration. A good clinicopathological response was obtained acutely with combination therapy of glucocorticoid and cyclosporine.